The origin of the Samaritans - Kartveit, Magnar, 1946- (Vetus Testamentum, Supplements, 2009)
Many Bible readers will think that chapter 17 of the second book of Kings refers to the origin of the Samaritans. This understanding of the chapter has its earliest attestation in the works of Josephus. The present book evaluates the methods often used for finding the origin of the Samaritans, makes an assessment of well known and new material, and ventures into some uncharted territory. It is suggested that the moment of birth of the Samaritans was the construction of the temple on Mount Gerizim. This happened in the first part of the fourth century bornc.e. in accordance with the original commandment of Moses in Deut 27:4.